Measurement and reduction of food loss and waste: Reconsidered - Ulrich Koester; Jens-Peter Loy; Yanjun Ren (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2018)
The number of recent publications on food loss and waste, and policy initiatives of governments and international organizations indicate the high priority of this topic. With this in mind, the methodology to measure food loss and waste has important implications for policy recommendations. The authors of this IAMO Policy Brief state that the many individual studies use different methodologies to quantify the size of waste with respect to metric measures and value for individual products and for the aggregate of food loss and waste. Most studies do not consider the costs incurred by reducing or redirecting food loss and waste. A recent publication has taken up the methodological problem (Bellamare et al.,2017). The authors of this IAMO Policy Brief investigate whether the proposed methodology solves the problem and can contribute to designing a rational policy to manage food loss and waste.
urn:nbn:de:gbv:3:2-96080
Keywords: 330